Doğrusal Olmayan İtme Analizi Yöntemi İle Performans Seviyesi Belirlenen Çelik Bir Yapının Yapısal Analizi - Altınağaç, Duygu (Fen Bilimleri Enstitüsü, 2016)
Deprem oluşumuna bağlı sismik etkiler dikkate alınarak tasarlanan günümüz yapılarında, yapı süneklik derecesi ve buna bağlı doğrusal olmayan davranış tipi önem arz etmektedir. Çelik yapıların malzeme niteliği açısından betonarme yapılara kıyasla son derece sünek davranış sergilemesi depremin hasar etkilerine karşı güvenli yapılar inşa edebilmek için tercih sebebi olmuştur. Doğrusal olmayan yapı davranışının analiz edilebilmesi için günümüzde pek çok bilgisayar destekli sayısal analiz programından faydalanılmaktadır. Bu programlar ile yapının kapasite eğrisini oluşturan tepe yer değiştirme istemi-taban kesme kuvveti ilişkisi, plastik mafsal oluşumu gibi doğrusal olmayan davranış özellikleri gözlemlenerek sistemin deprem davranışını belirleyen katsayı elde edilmektedir. Bu çalışma çerçevesinde doğrusal olmayan itme analizi yöntemi benimsenerek dört farklı şekilde yatay etkilere karşı güçlendirilmiş çelik çerçeve sistemi doğrusal olmayan statik tasarım yöntemi ve ETABS yapısal analiz programı ile değerlendirilmiştir. Elde edilen sonuçlara göre davranış katsayısı en yüksek olan ve imalat ve deprem sonrası hasarların onarım kolaylığı düşünülürek seçilen en ideal çapraz sistem üzerinden çalışmalar devam edilmiştir. Çelik yapının tasarımı ve boyutlandırılması Amerikan Çelik Yapılar Enstitüsü (American Institue of Steel Construction) 360-10 yönetmeliğine göre LRFD (Load and Resistance Factor Design) çözüm yöntemi uyarınca yapılmıştır. Tezin içeriği sekiz ana bölümden meydana gelmektedir. İlk bölümde çalışmanın amacı ve içeriği aktarılmaktadır. Burada incelenecek olan çelik sistemler ile ilgili tanımlayıcı bilgiler verilmesi amaçlanmıştır. Çelik çapraz sistemlerin incelenmesinin ardından bu çalışma kapsamında izlenecek ana tasarım stratejisi hakkında bilgiler aktarılmıştır. Performansa dayalı analizin temel prensiplerinin açıklandığı ikinci bölümde Amerikan Federal Acil Durum Yönetim Teşkilatı (Federal Emergency Management Agency) uyarınca taşıyıcı sistem hasar sınırları hakkında bilgi verilmiştir ve davranış katsayısı kavramı detaylıca incelenerek hesap yöntemleri sunulmuştur. Üçüncü bölümde çalışmanın bütününde kullanılan yöntemler ve teori hakkında bilgi verilerek şekil ve çizelgeler yardımıyla kavramlar daha anlaşılır şekilde ifade edilmiştir. Deprem Bölgelerinde Yapılacak Binalar Hakkında Yönetmelik 2007 uyarınca deprem tasarım spektrumları ve depreme göre tasarım yöntemleri bu bölüm içinde aktarılmıştır. Dördüncü bölümde ETABS V.15 yapısal analiz programı ile üç farklı modelin analizi yapılmış ve bu analiz sonuçlarının irdelenmesi ile oluşturulmuş plastik dönme kapasiteleri, tepe yer değiştirme istemi ve kapasite eğrisi sunulmuştur.Doğrusal olmayan davranış özellikleri tespit edilen sistemlerin incelenmesi ardından tercih edilen modelin tasarımı için gereken çelik yapı özellikleri, malzeme özellikleri, yük kombinasyonları ve yapıya etkiyen yükler beşinci bölümde ayrınıtıları ile aktarılmıştır. Beşinci bölüm ile tanımlanan yapısal özellikler ve ön tasarım koşulları çerçevesinde yapının boyutlandırılması için gerekli olan formüller AISC yönetmeliğine göre altıncı bölümde tanımlanmıştır. Ayrıca merkezi çelik çapraz sistemlerin plastik davranışının incelenmesinde yine Amerikan yönetmeliğinden faydalanılmış ve çapraz sistemin çevrimsel yükleme aşamalarındaki davranışı anlatılmıştır. Çelik yapının boyutlandırılması ile ilgili çözümler yedinci bölümde sunulmuştur. Burada çapraz, kolon ve kiriş elemanı boyutlandırılarak bağlantı elemanlarının tasarımı yapılarak matematiksel çözümler ile sunulmuştur. Sonuç bölümünde ise yapılan araştırmalar ve izlenen yöntemler neticesinde elde edilen çıkarımlar değerlendirilmiştir. Merkezi çelik çapraz sisteme ait yapının davranış katsayısının incelenen diğer sistemlere göre daha yüksek değerde oluşunun sebepleri açıklanmış ve analiz sırasında dikkat edilmesi faydalı olacak önemli noktalara değinilmiştir.

Todays structures are designed by considering the seismic effects occured by an earthquake, therefore ductility level and nonlinear behaviour became more important than early studies conducted in this field. In contrast to concrete elements, behaviour of a steel structure is more ductile under the loading effects of an earthquake. Steel structures are preferred by designers who are working to build safer buildings to resist seismic effects. In order to analyse the nonlinear behaviour of structures fast and safe, computational analyses are widely used by designers. By the help of graphical interfaces and solution steps of these programs, one can analyse a structure to get capacity curve that reflects the demand of tip displacement versus the base shear force on each step of loading and also plastic hinge locations which are the bases to understand nonlinear behaviour. Inelastic behavior of the materials and structures have been an important research field throughout years. Besides the advantages of inelastic nonlinear methods, inelastic behaviour of a material has to be limited with certain assumptions to have controlled yielding and rupture prevented structures. The result at this point is, inelastic design considerations allow designers to minimize costs by reducing sections and design prectically installed members while considering the limits of safety and security. Although equivelant seismic load method and response spectrum analysis method have been one of the most preferred methods for elastic-static analysis, they are not enough comprehensive to evaluate seismic effects on structures. A new approach "Performance Based Design" takes researchers a step further to investigate nonlinear behaviour of the structures. The reason behind why researchers adopted to use performance based design and analysis method is the need to understand the level of safety of structure and security of people inside building especcialy in earthquake effects. While previous methods of force-displacement relationships give engineers only an assumption of lateral load effects, performance based design methods provides comprehensive outputs as deformation and displacement characteristic of each structure and each member of the system. It is also discussed that structures should stay in pre determined damage limits without collapse while designing for earthquake resistance. R, response modification factor, represents the energy absortion capacity of a structure under inelastic behaviour. This coefficient comprimises damping and ductility ratio which used to reduce design forces while designing earthquake resistant structures. Within this study, four different types of lateral load resisting systems are analysed by using nonlinear static push over analysis method combined in ETABS structural analysis programme. The results are evaluated to select the model that has the highest response reduction factor and ease of manifacturing and maintenance after earthquake effects. Structural components of the steel structure is analysed by using the specifications defined by American Institue of Steel Construction (AISC-360-10) and solution method defined by Load and Resistance Factor Design (LRFD). This thesis incorporates eight chapters. The first chapter introduces the target of this study and gives a brief information about the types of models that will be analysed during following parts. Main principles of performance based nonlinear analysis method is defined in second chapter with the additional information provided from American Federal Emergency Management Agency (FEMA) and also detailed information is presented for the response reduction factor and techniques for the analytical explanations of the method. This method gives us the damage condition of the structure by using systems demand for displacements and deformations. Therefore, damage condition of a structure is the most basic and essential element to determine the performance of a structure under earthquake loading. Chapter three is divided between multiple sections of theories and methods that are used throughout this study and terms are detailed for more comprehensive understanding. Specifications for Buildings to be Build In Seismic Regions-2007 is used to calculate reponse spectrum of the site area and earthquake loads on the structure. Following this specification, soil conditions and first modal period of the structure need to be determined first to achieve response spectrum curve. Then, linear and nonlinear methods for earthquake analysis are followed by using the formulations given within this chapter. Nonlinear static push over analysis is conducted for three different models by ETABS V.15 computational program and plastic hinge capacities and capacity curve of all analysis are presented in tables in Chapter four. There are three different steel structures with different lateral load resisting systems like diagonal bracing, x type bracing and inverted v type bracing. The method adopted to perform nonlinear static pushover analysis is that the control point of the system (top floor diaphram) is pushed to target displacement limit by applying increasing lateral load. After the static pushover results are obtained for all three models, earthquake response modification factors are calculated by the given equations in chepter. By doing a comparison between models the most effective one is selected in terms of the highest response modification factor and ease of manifacturing and maintenance after earthquake effects. Chapter five lists the properties of the steel structure that are used in element sizing in the following section and bring in load breakdown that are applied to the structure. Material properties and load combinations are listed by using AISC specifications and the function of the building and the effect of location is explained by the selection of applied loads. Formulations for the structural sizing according to American Specifications are listed in Chapter six and cycling loading cases are detailed for the concentrically braced frames. When the system (concentrically braced framed system) is within the inelastic region it is expected that the compression elements will buckle and tension element will yield. While brace members are in yielding and buckling condition, beams and columns are designed to stay in elastic region. Chapter seven is constituted to represent detailed element analysis of the steel sections that are belong to the selected model by utilizing the specifications for seismic design of structural components. Column, beam and brace elements' capacities are checked against the unfavorable loading cases and connections between these elements are designed. Calculations are based on AISC 360-10 specification and LRFD solution method. At the final part of this study, overall results are presented by evaluating the performance of concentrically braced frame system under pushover analysis. It is observed that concentrically braced frames with improved topology has the highest performanse level in terms of response modification factor. All other models that are evaluated have at least 50% less energy absorbance compared to concentrically braced inverted v system. In addition to evaluations for all three models based on performance based nonlinear static pushover analysis. Due to high values of R factor compared with specification requirements, it is concluded that some parameters have more impact while doing computational based analysis rather than real structural situation. These are mainly the soil conditions, earthquake region and rigidity of structure. It is observed that when earthquake acceleration changes due to the effects of earthquake region and soil conditions, shear force acting on each floor changes. With the decrease in structure's weigh, lateral force acting on floors decrease accordingly. This results in inverse effect on strength factor and has an substantial increase in strength coefficient within R factor. All models that are analysed are three story buildings and the effect of vertical loads are more than lateral loads. This causes to large column sections and therefore increases the rigidity of the overall structure. Therefore lateral stifness of the overall structure gives us an increased R value. It is very important to design the connection of steel memebers to achieve a good level of ductility. In order to keep iterative force-displacement relationship and obtain capacity curve of the system without any rupture in elements of the steel braced system, these members should be designed considering the maximum forces applied during the cycling loading of the brace system. Local and global buckling is an other problem that need to be prevented during nonlinear analysis ofa steel brace frames. Width to thickness ratio of an element should be within required limits. By providing these properties of a steel brace member buckling can be revented an plastic hinges can occur at preferred locations. At the very end of the thesis some recommendations are given for future researchers.
Structural Analysis Of A Steel Frame Model Analysed By Nonlinear Push Over Analysis Based On Performance Based Design Criteria
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Performansa Dayalı Tasarım; Doğrusal Olmayan İtme Analizi; Yapısal Analiz; Çelik Çapraz Çerçeveler; Çelik Yapı; Performance Based Design; Nonlinear Push Over Analysis; Structural Analysis; Steel Braced Frames; Steel Structure